Synthesis, characterization and enhanced luminescence of terbium complexes with 2-pyrazinecarboxylic acid and butanedioic acid by inert-fluorescent lanthanide ions - 孔凯 张海霞 马瑞军 陈英楠 褚海斌 赵永亮 (Journal of rare earths, 2013)
Abstract： Ten solid terbium complexes with 2-pyrazinecarboxylic acid （Hpyca） and butanedioic acid （BDAH） were synthesized via coprecipitation method and characterized by elemental, EDTA titration, inductively coupled plasma （ICP）, thermogravim- etry-differential scanning calorimetry （TG-DSC） and infrared （IR） analyses. The results showed that the complexes had the composi- tions of Tb（pyca）（BDA）·2H2O, Tb0.5Y0.5（pyca）（BDA）·2H2O, Tb0.5La0.5（pyca）（BDA）·3H20, Tb0.5Gd0.5（pyca）（BDA）·2H2O, Tb0.7Y0.3（pyca）（BDA）·3HO, Tb0.7Lao.3（pyca）（BDA）-0.5H20, Tb0.TGd0.3（pyea）（BDA）＇H20, Tb0.6Y0.4（pyca）（BDA）·2.5H20, Tb0.6La0.4 （pyca）（BDA）·2.5H2O and Tbo.6Gd0.4（pyca）（BDA）·3H20. IR spectra indicated that the rare earth ions coordinated with the carboxylic oxygen atoms of Hpyca and BDAH. Luminescence spectra showed that the doped La3＋, y3＋ or Gd3＋ ions did not affect the lumines- cence emission peak positions, but remarkably increased the luminescent intensities of terbium complexes. Furthermore, the doped lanthanide complexes showed longer luminescence lifetimes and higher quantum yields than pure terbium complex. The enhanced luminescence efficiencies of Tb3＋ ions in the doped complexes might result from the antenna effect of the two carboxylate ligands as well as the decrease of the self-quench of the Tb3＋ ions induced by the doped lanthanide ions.